Acoustic communication in the Lusitanian toadfish, Halobatrachus didactylus: Evidence for an unusual large vocal repertoire - Amorim, Maria Clara Pessoa (2012)
The Lusitanian toadfish Halobatrachus didactylus (Bloch & Schneider) (Batrachoididae) is a well-known sound producer that has an unusual large acoustic repertoire for fish. This repertoire consists so far of five distinct sound categories: boatwhistles, grunt trains, croaks, double croaks and a mixed grunt–croak call. Sixteen males that spontaneously occupied artificial concrete nests placed in the intertidal zone of the Tagus estuary (Portugal) were recorded over 8 days in June/July 2006. During the analysis of the recordings new sound emissions were found. Long grunt trains that sounded to the human ear like a running engine were heard. These sounds differ from the normal grunt trains by having a lower amplitude, a much longer duration (tens of seconds versus ,1 second) and more grunts per call. Other new sound emissions (e.g. triple croaks) were also registered but were heard less frequently. The incidence of the various sound types is given.